RENAISSANCE DREAM CULTURES - Arcangeli, Alessandro. Link ([S.l.])
1 online resource
Keywords: This volume explores the dream cultures of the European long sixteenth century, with a focus on Italian sources, reflections and debates on the nature and value of dreams, and frameworks of interpretation.The chapters examine a variety of oneiric experiences, since distinctions such as that between dreams and visions are themselves culturally specific and variable. Several developments of the period are relevant and consequently considered, from the introduction of the printing press and the humanist rediscovery of ancient texts to the religious reforms and the cultural encounters at the time of the first globalisation. At the centre of the narrative is the exceptional case of Girolamo Cardano, heterodox physician, mathematician, astrologer, autobiographer, dreamer and key dream theorist of the epoch. The Italian peninsula produced the first printed editions of many classical and medieval treatises, and,particularly between the 1560s and the 1610s,was also especially active in the writing of texts, both Latin and vernacular, fascinated by the oneiric experience and investigating it. Given the role of the visual in dreaming, images are also analysed.This book will be a recommended reading for scholars, students and non-specialist readers of cultural history, Renaissance studies and dream cultures.